Digestibilidade e parâmetros ruminais de bovinos recebendo dietas de alto grão com grão de soja - Tavares, Daniel Henrique Souza (Universidade Federal do Tocantins, 2020)
This study aimed to evaluate the whole soybeans as a substitute for protein pellets in highgrain diets, with or without roughage, for cattle and its effects on dry matter (DM) and nutrients intake and digestibility, as well determine the ruminal and blood parameters. Four crossbred males cannulated in the rumen were used and distributed in a 4 x 4 Latin Square Design (four animals and four diets) in a 2 x 2 factorial arrangement, two sources of protein (protein pellet vs. whole raw soybean), with or without roughage (Mombasa grass silage corresponding at 15% of the dry matter of the diet). The trial lasted 80 days. There was a higher dry matter intake (DMI) for the diet with the pellet compared to the diet with soybeans (P = 0.04, 13.57 vs. 9.91 animal-1 day-1). The inclusion of roughage in the diet increased DMI (P = 0.05). Crude protein intake was not affected by protein sources or inclusion of roughage (P> 0.10). The inclusion of roughage in the diet allowed an increase in the neutral detergent fiber intake (P <0.01), while the use of soybeans did not change the ether extract intake (P> 0.10). The use of the soybean replacing the pellet and the inclusion of 15% roughage in the diet promoted a similar diets total digestible nutrients intake (TDN) (p> 0.10) with an average of 8.71 kg day -1. There was no influence of diets on the digestibility of DM, CP or TDN of the diets (P> 0.10), 0.57; 0.49 and 74.47%, respectively. Greater total carbohydrates digestibility was observed for diets without roughage (0.73 vs. 0.56). The diets with roughage had a ruminal pH mean higher than those without roughage (P = 0.10), 6.13 vs. 5.77. The use of soybeans in the diet allowed a similar concentration of ruminal ammoniacal nitrogen (P> 0.10), 5.26 mg, when it was compared to the use of the protein pellet. There was also no influence of diets on plasma levels of urea, total proteins, albumin, triglycerides, creatinine, AST and ALT (P> 0.10). Higher amounts of cholesterol and glucose were found in the plasma of animals fed soybeans as a protein source (P = 0.05). The use of whole raw soybean as a protein source in high-grain diets for cattle reduces the intake of dry matter, however, it allows to keep the intake of nutrients and NDT without changing the ammonia nitrogen levels and rumen pH, in addition to maintaining blood parameters within normal concentrations. The supply of 15% silage in a high-grain diet for feedlot cattle increases the dry matter intake and maintains the energy intake of the diet, in addition to maintaining the average ruminal pH above 6.0.